PENGARUH KOMPETENSI PERSONIL, KEPRIBADIAN DAN TEAM WORK TERHADAP KUALITAS LAYANAN DI POLRES MUNA - Firmansyah Mane; Rahmat Madjid; Laode Asfahyadin Aliddin (Pascasarjana Universitas Halu Oleo, 2021)
This study aims to determine the effect of personnel competence, personality, and team work on the quality of service at the Muna Police. This research approach is a survey with an explanatory research design. Data was collected in a cross section by using an instrument in the form of a questionnaire or questionnaire. The population of this study were all members of the National Police at the Muna Police Station, Southeast Sulawesi Province. The size of the research sample was 82 people using a random technique based on strata (stratified proportional random sampling). Data analysis with descriptive analysis and Multiple Linear RegressionThe results showed that competence, personality, and team work had a positive and significant effect either simultaneously or partially on service quality. Thus it can be said that changes in competence improvement are reflected through improvements, skills and attitudes; personality reflected through interpersonal relationships, friendliness, conscientiousness, emotional stability and openness to experience, as well as teamwork reflected through high participation, open communication, listening to members well, sharing leadership, and self-assessment have positive and significant contributions in supporting improvement of service quality at the Muna Resort Police..